PENGARUH INTENSITAS SCREEN TIME TERHADAP KECENDERUNGAN OVERTHINKING PADA REMAJA - Ria Safaria Sadif; Unhaluddin T Kurniawan; Hera Asmara (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to examine the effect of screen time intensity on the tendency toward overthinking among adolescents. The research employed a quantitative approach using an ex post facto design. The sample was selected through purposive sampling based on criteria relevant to the research objectives. Data were collected using a screen time intensity scale and the Ruminative Response Scale (RRS-10) to measure the tendency toward overthinking. Data were analyzed using simple linear regression. The findings indicate that screen time intensity has a significant effect on adolescents' tendency to engage in overthinking. Higher durations of digital device use are associated with a greater likelihood of repetitive, excessive, and difficult-to-control thoughts. These findings suggest that digital media use is closely related to adolescents' psychological well-being. Therefore, more responsible and balanced screen time management is essential to maintain mental health and support optimal psychological development among adolescents.